Some results of interfacing the r-r coincidence spectrometer and computer - Trinh, Chu Duc; Quang, Nguyen Vinh; Lam, Nguyen Dang; Khang, Pham Dinh (VNU Journal of Science: Mathematics - Physics; Vol 18 No 3, 2002)
Abstract